Role Synthesis of Pediatric Palliative Nurse in Ramathibodi Hospital : Document Research - Khunin, Nitcha; Prichayudh, Nitaya; Chatgitisan, Aunchalee; Junda, Tiraporn (Journal of Nursing, Siam University, 2021)
This Article is documentary research to synthesize the role of pediatric palliative care nurse (PPCN) at Ramathibodi hospital. The example was 100 patients who had document of palliative nurse’s notes who was received in hospital more than 48 hours during 1 January 2017 – 31 December 2018. The role of PPCN extends to The concept of Watson’s 10 carative factors and the end-stage patients support of Phra Paisal Visalo. Follow the research: 1) Read the palliative nurse’s notes carefully 2) Find the importance and add Identification code 3) Identify content and find associations for groups 4) Finding correlation for each category. And then synthesis is the role of PPCN. Research result show that the role of PPCN has set this up. 1) Provide health care advice and death according to the level of awareness and the sensitivity of each age 2) Assess the problems, support and strengthen the health of physical, mental, emotional, social and soul for the young patients and families 3) Prepare a joint planning between the multidisciplinary and families 4) Pain management and care for happiness and peace of mind. Reduce fear from being in the hospital or performing procedures 5) Bring about goodness and help patients and families with peaceful mind 6) Coordination 7) Care at the end of palliative care. This research showed that PPCN’s role play an important of the health team approaches covering holistic care to build trust, understanding and acceptance of the patients and families all the way to the end of life to pass away peacefully. And resulting in reduced feelings of loss and grieves.